Perawatan Mulut (Oral Hygiene) menggunakan Obat Kumur Daun Sirih untuk Mencegah Gangguan Mulut Lansia - Elizabeth Yun Yun Vinsur; Nanik Dwi Astutik; Oktavia Indriyani (Yayasan Inspirasi El Burhani, 2022)
Introduction: Older people have a complexity of health status, systemic diseases, and the use of certain medications creates oral health problems. Indonesian people, use quite a lot of family medicinal plants, for example a decoction of betel leaves (Piper betle L.). Its compounds are known to have strong potential as an anti-fungal and anti-bacterial. The role of nurses is to increase the knowledge of health cadres through health counseling activities about the basic concepts of oral hygiene and how to make betel leaf-based mouthwashes Objective: The counseling activity aims to increase the knowledge of health cadres about oral hygiene and about how to make mouthwashes made from betel leaves. Method: The implementation has been held in June 2022. The number of participants was 14 people. The participants are health cadres in Wonosari Hamlet. The instruments used to evaluate were ten (10) pre-test and post-test questionnaire questions and a checklist of procedures for how to make betel leaf-based mouthwashes. The data on the results are presented in the form of a table of scores. Result: The average score of knowledge about oral hygiene are increase from 49.29 to 67.27. Procedure evaluation score 97.61%. Conclusion: There was an increase in knowledge about oral hygiene and representatives of cadres were able to make Betel Leaf Mouthwash. It is hoped that it can be done to the elderly so that the optimization of PHC in terms of oral hygiene of the elderly uses betel leaf mouthwash to prevent oral disorders from manifesting.